'All I have to do is dream?' Re-greening Irish integrationism - LENTIN, RONIT (My University, 2010)
Contemporary Ireland had moved from the discovery ? during the 1997 European Year against Racism ? that racism is indeed an Irish problem, to euphemisms such as interculturalism, transculturalism, integration and cultural diversity. Up until the last throes of Celtic capitalism, the dominant narrative was one of failed European multiculturalism and the suggestion that `we? were getting it right while other EU states were getting bogged down in assimilationism and multiculturalism ? both seen as failed migrant integration technologies. However, as the economy sinks, these discourses have totally disappeared from the public radar, as integration and immigration become vague memories of better times, or discourses of renewed competition for what are clearly scarce resources. At the same time, race and racism are becoming unspeakable, spoken only by the white, settled, Christian Irish advocates of solidarity and `interculturalism?, making no space for the racialised to partake in the antiracist conversation.
PUBLISHED
Keywords: integration; migrants